Pengaruh Pelatihan Harga diri terhadap penyesuaian diri pada remaja - Faridah Ainur Rohmah (HUMANITAS: Indonesian Psychological Journal, 2004)
The study intends to know the effect of self esteem training to self adaptation of adolescent. The subject are 22 students of MAN I Yogyakarta who have high self adaptation of problems. They didive into two groups: experiment group and control group.The data is analyzed by man witney. The result shows that before research the condition of experiment and control group is not different in self adjusment. After research, there is adjustment between experimental group and control group (u = 3.0,<0.001). Thus the research show there is affect of self esteem training to self adjusment of adolescent.